Characterization of oxytocin and vasopressin receptors in the Southern giant pouched rat and comparison to other rodents - Freeman, Angela R.; Arenas, Samanta; Lee, Danielle N.; Singh, Bhupinder; Ophir, Alexander G. (Frontiers in Endocrinology, 2024)
Vasopressin and oxytocin are well known and evolutionarily ancient modulators of social behavior. The distribution and relative densities of vasopressin and oxytocin receptors are known to modulate the sensitivity to these signaling molecules. Comparative work is needed to determine which neural networks have been conserved and modified over evolutionary time, and which social behaviors are commonly modulated by nonapeptide signaling. To this end, we used receptor autoradiography to determine the distribution of vasopressin 1a and oxytocin receptors in the Southern giant pouched rat (Cricetomys ansorgei) brain, and to assess the relative densities of these receptors in specific brain regions. We then compared the relative receptor pattern to 23 other species of rodents using a multivariate ANOVA. Pouched rat receptor patterns were strikingly similar to hamsters and voles overall, despite the variation in social organization among species. Uniquely, the pouched rat had dense vasopressin 1a receptor binding in the caudate-putamen (i.e., striatum), an area that might impact affiliative behavior in this species. In contrast, the pouched rat had relatively little oxytocin receptor binding in much of the anterior forebrain. Notably, however, oxytocin receptor binding demonstrated extremely dense binding in the bed nucleus of the stria terminalis, which is associated with the modulation of several social behaviors and a central hub of the social decision-making network. Examination of the nonapeptide system has the potential to reveal insights into species-specific behaviors and general themes in the modulation of social behavior.